2013
DOI: 10.1017/s1368980013002231
|View full text |Cite
|
Sign up to set email alerts
|

Use of food label information by urban consumers in India – a study among supermarket shoppers

Abstract: Objective: To study consumer knowledge and use of food labels. Design: A cross-sectional study employing both quantitative and qualitative methods. Intercept interviews were conducted with 1832 consumers at supermarket sites selected using a stratified random sampling procedure. This information was triangulated with twenty-one focus group discussions. Setting: New Delhi and Hyderabad, two metro-cities from north and south India. Subjects: Adolescent (10-19 years), adult (20-59 years) and elderly ($60 years) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
54
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 19 publications
8
54
1
5
Order By: Relevance
“…Consequently, lack of time and excess of information have been referred as the most important factors answered by respondents. This behaviour may explain the higher frequency of reading the product shelf‐life (Vemula, Gavaravarapu, Mendu, Mathur, & Avula, ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, lack of time and excess of information have been referred as the most important factors answered by respondents. This behaviour may explain the higher frequency of reading the product shelf‐life (Vemula, Gavaravarapu, Mendu, Mathur, & Avula, ).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that mother's level of understanding about healthy nutrition was significantly related to the food-related behaviours of their children. On the other hand, a study by Vemula et al suggested that the effort to promote healthy food choices through the use of food labels is not completely effective (Vemula et al, 2013). In this context, our results suggest that in addition to increasing the amount of nutrition information received by parents, it is important to improve the quality of information and utilisation of this information by the mothers.…”
Section: Discussionmentioning
confidence: 53%
“…The nutritional information presented on the food label, however, is approached in very technical terms and difficult language to understand for a large part of the population (Hieke & Taylor, 2012). This high complexity may be one of the reasons why consumers lack the habit of reading food labels and end up disregarding them as an aiding tool at the time of purchase (Bendino et al, 2012;Vemula et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This difficulty is faced worldwide, which makes evident the need for constant reformulation of food labels (Vemula et al, 2014). On this sense, the development of a simpler label with ratings could enable a better understanding of the nutritional information by the consumer and, therefore, facilitate the practice of healthier eating habits (Sanz-Valero et al, 2012;Robert & Khandpur, 2014).…”
Section: Introductionmentioning
confidence: 99%